Study Program Discipline as A Learning Organization in Maintaining Performance Due to The COVID-19 Pandemic - Bayu Antrakusuma; Teti Novianti; Muhammad Japar (PAEDAGOGIA, 2024)
This study aims to determine the discipline of the Bachelor of Science Education Study Program Faculty of Teacher Training and Education Universitas Sebelas Maret (BSESP FTTE UNS) as a learning organization in maintaining performance due to the COVID-19 pandemic. This research uses a post-positivism approach with qualitative methods. Data were collected through in-depth interviews with several informants. Based on the results of the discussion, it can be concluded that the BSESP FTTE UNS maintains performance as a learning organization during the COVID-19 pandemic through five disciplines according to Peter Senge, namely: 1) System Thinking, maintaining the commitment of organizational members in maintaining the sustainability of the organizational work system through the leadership of the head of the study program; 2) Personal Mastery, providing opportunities for each member of the organization to participate in activities to improve their competence; 3) Mental Models, providing appeals, and the right decisions in dealing with the COVID-19 pandemic; 4) Shared Vision, having a shared vision and ultimate goal that is still realized in learning, research, and community service activities, even though they have to adapt to changes; and 5) Team Learning, maintaining the Research Group to keep running even though it has to adapt to limitations